What Determines the Effectiveness of a Currency: A Composite Index - Karakostas, Emmanouil (International Journal of Applied Economics, Finance and Accounting, 2022)
The variety and diversity of currencies forms a significant aspect of the international political economy and especially the global economic relations among countries. It can be said that the “language” of countries’ international economic activities is the variation displayed by their currencies. A plethora of papers has indicated a relationship between exchange rates and many facets of international economic relations, with a negative, positive, or even neutral link. Exchange rates can fluctuate due to exogenous events or due to endogenous choice. Whatever the cause, it is certain that exchange rate fluctuation can influence many features of a country’s economy. Specifically, exchange rates can affect macroeconomic variables, trade performance and others. So, what are the prerequisites that shape the relationship between a country’s exchange rates and its economic activities? These prerequisites include the international, political and economic aspects of a country. The combination of these factors is what shapes the country’s relative effectiveness and its “freedom” to use its currency to achieve its economic goals. The current paper shows that the combination of the international, political and economic aspects of a country is fundamental to its freedom to use its currency for this purpose. The methodology adopted is the creation of a Composite Index.